Pengaruh Perceived Value, Kualitas Produk, dan Citra Merek terhadap Loyalitas Pelanggan (Studi Kasus pada Pelanggan Produk Susu Ultra Milk di Kota Bogor) - Zuheratul Kamal; Agus Pranamulia; Dewi Fitrianti (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of perceived value, product quality, and brand image on customer loyalty among Ultra Milk UHT milk consumers in Bogor City. The sample used in this study consisted of all Ultra Milk dairy product consumers in Bogor City, with 150 respondents. The analysis method used was multiple linear regression analysis, with perceived value, product quality, and brand image as independent variables and customer loyalty as the dependent variable. Using 150 respondents as a sample, the results of the study show that perceived value, product quality, and brand image have a significant effect on customer loyalty, both partially and simultaneously, where partially perceived value has the greatest influence on customer loyalty.